Preparation of synbiotic fermented milk and evaluation of short-chain fatty acids production during storage study - Hati, Subrota; Mitali; Dr; Dr (Indian Journal of Dairy Science, 2024)
The fermented milk product was formulated using Lactobacillus cultures V3 and M5 with addition of corn-starch. Addition of 8% sugar was selected for the preparation of fermented milks based on various sensory attributes and overall acceptability. Optimized fermented milk (T) along with control where corn starch was replaced with skim milk powder (C) were analyzed for theirproximate composition, short chain fatty acids (SCFAs) production as well as changes in physico-chemical and sensory properties during storage at refrigerated temperature (5±2ºC) up to 28 days. The pH of fermented milks C and T had significant (P<0.05) differences during 28 days of refrigerated storage and decreased from 4.35 to 3.85 and 3.93, respectively. Acidity (% LA) of fermented milks C and T significantly (P<0.05) increased to 1.22% from 0.78 and 0.76%, respectively during storage. Average viable counts (log CFU/ml) of fermented milk T was 9.57 log CFU/ml, which decreased to 7.36 after 28 days, which had no significant differences with C. All three short chain fatty acids (SCFA), acetic acid, propionic acid and butyric acid content (μg/mL) of fermented milks C and T significantly (P<0.05) increased during storage from 1.27 to 5.37 and from 4.17 to 11.00μg/mL, 2.00 to 2.40 and from 2.52 to 3.64 μg/mL, 2.25 and 4.72 from 2.11 and 3.18 μg/mL, respectively during storage. Treated Fermented milks were acceptable up to 21 days under refrigeration temperature (5±2 ºC) and obtained higher Sensory scores for all the attributes which decreased with elevated storage period.